Expressive Speech Action Study Of Rocky Gerung: Youtube Iso-Late Show - Fathiah Riadianti; Futi Hamdiyah Telaumbanua; Wulan Nurhasanah; Ahmad Yuhdi (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
This research aims to analyze the expressive speech acts of the character Rocky Gerung. This type of research uses a descriptive method with a qualitative approach. Data collection techniques in this research used note-taking techniques, listening techniques and documentation techniques. The expressive speech act of criticizing is 4 utterances, the expressive speech act of complaining is 3 utterances, and the expressive speech act of expecting something/desire is 4 utterances. The main theme discussed by this figure is the world of politics in the state. And the public's responses and comments regarding Rocky Gerung's statement varied greatly by looking at the comments on the YouTube channel video.